Teacher ethics in wisdom-based educational innovation: a cross-cultural analysis - Endang Wuryandini; Gildan Jaya Muhammad Ramadhan; Achmad Agung (Lentera Negeri, 2026)
This integrative review examines how teacher ethics shapes the implementation of local wisdom-based educational innovation in Indonesian education. Local wisdom-based educational innovation is operationalized as the deliberate integration of locally rooted cultural knowledge, values, languages, social practices, and ecological understandings into curriculum, pedagogy, learning media, assessment, school culture, or school-community collaboration, subject to ethical principles of justice, care, inclusiveness, and respect for human dignity. Sources were identified and bibliographically verified through ERIC, DOAJ, Crossref-linked publisher records, journal platforms, and official Indonesian policy repositories using Boolean combinations of "local wisdom," "culture-based education," "ethnoscience," "educational innovation," "teacher ethics," "character education," and "culturally responsive teaching." Journal articles published mainly in 2020-2025 were prioritized, while foundational peer-reviewed studies were retained when theoretically necessary. The final corpus comprised 27 peer-reviewed journal articles and four official policy/legal documents. Data were organized in a source-level evidence matrix and analyzed thematically using a predefined codebook and a second-pass consistency check. Five themes emerged: pedagogical integration, teacher ethical agency, character and identity formation, digital adaptation, and ecosystem challenges. The synthesis shows that local wisdom is most educationally meaningful when teachers critically select cultural values, translate them into contextual learning, ensure inclusion and justice, and connect local identity with digital innovation. Teacher ethical reflection therefore functions as a governing mechanism that determines whether local wisdom becomes transformative pedagogy or merely ceremonial cultural representation.